The Primary and Secondary Corporate Credit facilities - Nina Boyarchenko; Caren Cox; Richard K. Crump; Andrew Danzig; Anna Kovner; Or Shachar; Patrick Steiner (Federal Reserve Bank of New York, 2021)
The Federal Reserve introduced the Primary Market Corporate Credit Facility (PMCCF) and the Secondary Market Corporate Credit Facility (SMCCF) in response to the severe disruptions in corporate bond markets triggered by the COVID-19 pandemic and subsequent economic shutdowns. The Corporate Credit Facilities (CCFs) were designed to work together to restore functioning of credit markets, with an overarching goal of facilitating credit provision to the non-financial corporate sector of the U.S. economy. This paper provides an overview of the CCFs, including detailing the facilities' design, documenting their operations and usage, and describing their impact on corporate bond markets.
Keywords: G12; G18; G19; 330; Federal Reserve; corporate bond markets; corporate credit facilities; PMCCF; SMCCF; Federal Reserve lending facilities